2021
DOI: 10.1016/j.celrep.2021.108877
|View full text |Cite
|
Sign up to set email alerts
|

The ribosome collision sensor Hel2 functions as preventive quality control in the secretory pathway

Abstract: Highlights d Selective ribosome profiling reveals endogenous Hel2 substrates d Hel2 binds preferentially to the pre-engaged secretory RNCs d Hel2 recruitment to secretory RNCs is elevated by loss of SRP d Hel2-mediated QC alleviates mitochondrial dysfunction because of the lack of SRP

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…This non-canonical binding of SRP is still dependent upon the ribosome and in some cases requires features of the 3′ UTR, but it is not presently known how preferential pre-delivery of SRP to these substrates occurs and if it requires specific mRNA binding proteins [ 29 ]. Interestingly, it was recently shown that the ribosome-associated factor, Hel2, which binds to collided ribosomes that arise where stalling occurs, was shown to bind to membrane protein polysomes in a pattern that strongly overlaps with that of SRP [ 61 ].…”
Section: Srp-dependent Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…This non-canonical binding of SRP is still dependent upon the ribosome and in some cases requires features of the 3′ UTR, but it is not presently known how preferential pre-delivery of SRP to these substrates occurs and if it requires specific mRNA binding proteins [ 29 ]. Interestingly, it was recently shown that the ribosome-associated factor, Hel2, which binds to collided ribosomes that arise where stalling occurs, was shown to bind to membrane protein polysomes in a pattern that strongly overlaps with that of SRP [ 61 ].…”
Section: Srp-dependent Targetingmentioning
confidence: 99%
“…In the absence of SRP, substrates that are usually delivered to the ER can become aggregated [ 62 ] or are instead mistargeted to mitochondria causing disruption to mitochondrial function [ 56 , 60 ], a phenotype also observed if Hel2 is disrupted [ 61 ]. Hence, another key function of SRP is to prevent promiscuous misbehaviour of hydrophobic targeting signals.…”
Section: Srp-dependent Targetingmentioning
confidence: 99%
“…Recognition and binding of SP or TMD occurs co-translationally, as the synthesized peptide is released from the ribosomal tunnel. Other proteins may be involved in this process [ 22 ]. After recognition, one of the SRP domains blocks the elongation cycle, and the mRNA/ribosome/nascent peptide/SRP complex is transported to the ER membrane, where SRP binds to its membrane receptor, SR. A special multisubunit protein complex—the translocon (Sec61-complex), which forms a channel in the ER membrane, participates in the binding of the ribosome to the ER and in the translocation of the peptide across the membrane [ 23 , 24 ].…”
Section: Translation Associated With Er Membranesmentioning
confidence: 99%
“…More recently, the picture has become even more complicated due to the emergence of a new player— the HEL2/ZNF598 protein, a component of the RQC system [ 22 ]. In yeast, this protein is probably capable of additional control of SP recognition by the SRP particle and delivery of the corresponding mRNA to the translocon.…”
Section: Translation Associated With the Outer Mitochondrial Membranementioning
confidence: 99%
“…Nonetheless, it remains elusive whether or not the co-translational ER-RQC is indeed linked to the post-translational ERAD pathway (66,70). A yeast homolog of the ribosome collision sensor ZNF598 has also been shown to titrate the expression of misfolded ER transporter (70) and associate with mRNAs encoding secretory proteins to minimize their defective targeting to mitochondria (71). However, the latter may not occur at the ER translocon.…”
Section: Subtypes Of Rqc Pathways: Er-rqcmentioning
confidence: 99%